Cultural Heritage Zoning System of Otanaha Fort Gorontalo City: Its Implementation in Regional Regulations - Andi Muliadi (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to determine and analyze the implementation of the zoning system in the cultural heritage of Fort Otanaha in Gorontalo Province. This research uses a type of normative-empirical (applied) research, which is research that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on a certain legal event that occurs in society. Based on the results of the study, it was concluded that in the application of the zoning system in accordance with the mandate of applicable laws and regulations, it is necessary to have a legal umbrella, namely a derivative regulation that can become a legal umbrella and become an extension to realize the mandate stated in the Cultural Heritage Law so that the cultural heritage of Fort Otanaha can be preserved and passed down from generation to generation.